Clinical features of chronic hepatitis C in children - M. S. Bokhonov; L. E. Galitsina; I. G. Sitnikov; O. S. Gorbunova (LLC "Diagnostics and Vaccines", 2023)
The problem of chronic viral hepatitis C is one of the most urgent in modern medicine. This cannot but concern the child population, which is the most vulnerable. Under supervision were 50 children under 18 years of age who were treated in the infectious diseases clinical hospital in Yaroslavl. Chronic hepatitis C in children in 56% is asymptomatic, and only in 44% of patients ALT values exceeded the norm. The asymptomatic course of CHC does not mean the absence of disease progression. Liver elastometry revealed fibrosis of varying severity in the absence of clinical symptoms of the disease. The distribution of genotypes in children corre- sponded to that in adults, but genotype 2 was detected more often than in adults. Viral load often had a minimum level, in contrast to the adult population of the Yaroslavl region.